Cardiometabolic consequences of PCOS - Podgórska, Klaudia; Puła, Aleksandra; Krzysiek, Urszula; Artykiewicz, Klaudia; Gorczyca, Kamila; Kozieł, Paweł; Grodkiewicz, Maria; Słupczyńska, Aleksandra; Urbaś, Weronika; Czarkowski, Marcin (Journal of Education, Health and Sport, 2022)
Polycystic ovary syndrome (PCOS) is a heterogeneous disorder in terms of clinical symptoms and laboratory findings. It is one of the most common endocrinopathies in women of childbearing age. The development of symptoms and the degree of severity in the course of the disease are the results of changes in the ovaries which may be caused by many genetic, metabolic, neuroendocrine, and environmental factors. The main clinical manifestations are menstrual disorders, difficulties with becoming pregnant, and changes related to hyperandrogenism, e.g., acne, hirsutism. Recognition is above mainly based on Rotterdam criteria. A comprehensive explanation of pathophysiology is still lacking. Nevertheless, it probably is a multifactorial condition with a genetic component. Women suffering from PCOS experience lipid and carbohydrate metabolism disorders, which lead to insulin resistance, obesity, hypertension, and cardiac complications. Insulin resistance affects 65-70% of women and not only plays a significant role in the development of the disease but also contributes to the development of hypertension and dyslipidemia. Potential mechanisms of hypertension in PCOS include endothelial dysfunction, increased aldosterone, and excess testosterone secretion, whereas lipid abnormalities consist of reduced high-density lipoprotein-cholesterol (HDL-C), increased triglycerides, and low-density lipoprotein-cholesterol (LDL-C). All of these factors cause high cardiovascular risk. Currently, therapy considers both lifestyle improvements and medications and must be tailored on a case-by-case basis. It is very important not to consider PCOS only in the context of gynecological and endocrine diseases, but also metabolic changes and cardiovascular diseases. Treatment of PCOS should be individualized and dependent on the predominant disorders, as well as the short- and long-term goals chosen. It also should take the prevention of cardiovascular diseases into account.